2021
DOI: 10.1111/ijmr.12258
|View full text |Cite
|
Sign up to set email alerts
|

The safety–quality dominant view of food chain integrity: Implications for consumer‐centric food chain governance

Abstract: Food chain integrity demands strengthening the position of end consumers in the food system. Shaping this consumer-centric agenda leads to a multidimensional quest where actors in the food chain need to remodel their production, processing and disclosure norms by focusing on end consumers' expectations. Food chain integrity so far has largely been explained using the angles of fraud and criminality to mainstream the criticality of curbing intentional contamination in food chain operations. However, the view wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Indeed, food serves as an "imperative contributor to destination tourism because of its capability to influence tourists' perceived image and food satisfaction" (Chi et al, 2013, p. 99). In the food system, consumers' roles must be strengthened to maintain food chain integrity, and a study in this context showed that the relationship between food safety and food quality of food chain integrity sets the basis for advanced governance mechanisms, such as food transparency and food authenticity (Roy and Srivastava, 2022).…”
Section: Food Culture and Festival Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, food serves as an "imperative contributor to destination tourism because of its capability to influence tourists' perceived image and food satisfaction" (Chi et al, 2013, p. 99). In the food system, consumers' roles must be strengthened to maintain food chain integrity, and a study in this context showed that the relationship between food safety and food quality of food chain integrity sets the basis for advanced governance mechanisms, such as food transparency and food authenticity (Roy and Srivastava, 2022).…”
Section: Food Culture and Festival Attributesmentioning
confidence: 99%
“…, 2013, p. 99). In the food system, consumers' roles must be strengthened to maintain food chain integrity, and a study in this context showed that the relationship between food safety and food quality of food chain integrity sets the basis for advanced governance mechanisms, such as food transparency and food authenticity (Roy and Srivastava, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The first strand of literature focusses on factors influencing how consumers and firms view FQ and how FQ and safety jointly contribute to food chain integrity (e.g. food crime, fraud, transparency and authenticity) (Chamhuri and Batt, 2015;Petrescu et al, 2019;Roy and Srivastava, 2022). Using data from Belgium and Romania, Petrescu et al (2022) analysed how consumers evaluate the relevance of environmental-social indicators to FQ.…”
Section: Introductionmentioning
confidence: 99%
“…food crime, fraud, transparency and authenticity) (Chamhuri and Batt, 2015; Petrescu et al. , 2019; Roy and Srivastava, 2022). Using data from Belgium and Romania, Petrescu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation